In vitro ACE2 Enzyme Inhibitory Activity Evaluation of Different Salvia Essential Oils - Karadağ, Ayşe Esra; Biltekin, Sevde Nur; Demirci, Betul; Demirci, F. B. (Istanbul Medipol University, 2022)
In this present study, commertially available Salvia triloba L., S.officinalis L., and S. sclarea L. essential oils were evaluated for their in vitro angiotensin converting enzyme 2 (ACE2) inhibitory activity. The Salvia essential oils compositions were confirmed both by GC-FID and GC/MS. Main components of the S. triloba essential oil was characterized as 1,8-cineole (22.8%), camphor (17.2%), ?-thujone (15.2 %), ?-caryophyllene (11.4 %), and ?-humulene (3%). Major constiutents were identified as ?-thujone (28.5 %), camphor (20.6 %), 1,8-cineole (10.9%), ?-humulene (5%), and camphene (4.9 %) in S. officinalis essential oil. Whereas, linalylacetate (56.8 %), linalool (21.1%), ?-terpineol (6.1%), geraniol (5%), and ?-caryophyllene (3.4%) were the major components of S. sclarea essential oil. The essential oils were evaluated using a fluorometric multiplate based enzyme inhibition kit, where the ACE2 inhi-bitions of S. triloba, S. officinalis, and S. sclarea essential oils were 50.1%, 60.5%, and 72.1% at a concentration of 20 µg/mL, respectively. As a result, further tests of Salvia essential oils supported by in vivo studies may have antiviral potential ap-plications against coronaviruses due to ACE2 enzyme inhibitions. © 2022, Istanbul Medipol University. All rights reserved.
Keywords: ACE2; coronavirus; essential oil; Salvia